Not for Lack of Trying: American Entrepreneurship in Black and White - Philipp Koellinger; Maria Minniti (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Using a sample obtained from a survey conducted in the United States during summer 2002, we study the variables related to observed differences in the rate of entrepreneurial involvement between black and white Americans. We find strong evidence that differences in subjective and often biased perceptions are highly associated with entrepreneurial propensity across these two racial groups. In addition, we find that black Americans tend to exhibit more optimistic perceptions of their business environment than other racial groups and are more likely than others to attempt starting a business. In fact, our results show that blacks are almost twice as likely as whites to try starting a business. Thus, our results suggest that the under representation of black Americans among established entrepreneurs is not due to lack of trying but may instead be due to stronger barriers to entry and higher failure rates.
Keywords: J15; M13; D01; J23; 330; Entrepreneurship; Black Entrepreneurship; Minority Entrepreneurship; Nascent Entrepreneurship